THE POSITIONING TOURISM ENTERPRISE ON THE TOURIST MARKET OF UKRAINE - O. Ivanenko (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
The article analyzes the competitiveness of tourism on the basis of integrated assessment of the tourist market. Developed a system of indicators to justify rated financial condition of tourism enterprises of Ukraine. Use rating Tour operator based integrated assessment possible to identify three groups of tourism enterprises: high, medium and low integrated assessment and to evaluate differences in responses by the rating and ranking based on integrated assessment.